IDENTIFICATION OF PRODUCTION COSTS IN TEMPE UD MAWAR SARI AGROINDUSTRY IN UTEUN BAYI VILLAGE BANDA SAKTI SUB-DISTRICT LHOKSEUMAWE CITY - Irada Sinta; Asmaul Husna; Rico Nur Ilham (SEAN Institute, 2023)
The purpose of this study was to see the effect of identification of production costs in Tempe Agroindustry UD Mawar Sari in Uteun Bayi Village, Banda Sakti District, Lhokseumawe City. The data analysis method used in this Field Work Practice is a quantitative descriptive method, namely analyzing and describing data on business operational activities, especially those related to production costs, namely raw material costs, labor costs and overhead costs at Tempe Agro-industry UD Mawar Sari. This study uses primary and secondary data types. The results showed that in the tempe production process at the Tempe Agro-industry UD Mawar Sari the results of the identification of production costs were Rp. 420,775,433.3 which was obtained from raw material costs of Rp. 342,060,000, - labor costs of Rp. 31,559,200 ,-,